Cardamonin induces apoptosis in human nasopharyngeal carcinoma cells via mitochondrial death pathway mediated by caspase-3 and caspase-8 activation, independent of caspase-9 signalling responses - Chiang, Michelle (2016)
Nasopharyngeal cancer lies in the upper part of throat behind the nose and near the base of the skull called the nasopharynx. It is more commonly diagnosed in parts of Asia, particularly in the southern China. Five local edible plants from different families; namely curry leaf (Murraya koenigii), temu kunci (Boesenbergia rotunda), spring onion leaf (Allium cepa), mushroom bean (Phaseolus vulgaris) and bunga kantan (Phaeomeria imperialis) were macerated to obtain methanol, ethyl acetate and hexane crude extracts. Each crude extract was tested against nasopharyngeal carcinoma (HK-1) and normal nasopharyngeal epithelial (NP-69) cell lines. All crude extracts from temu kunci (Boesenbergia rotunda) were found to contain flavonoids, alkaloids and polyphenols. Both methanolic and hexane crude extracts were found to exhibit cytotoxic effects against HK-1 cells but non-toxic against NP-69 cell line. Of all the bioactive compounds previously extracted from B. Rotunda, we have selected four commercially available flavonoids and polyphenols to narrow down our search to one potential anticancer agent. These compounds were tested against HK-1 and NP-69 cell lines for cytotoxicity and it was found that cardamonin exhibits highest cytotoxic effect against HK-1 cells with IC50 of 22 μg/mL.